THE DEVELOPMENT OF VERBAL INTELLIGENCE OF A TEACHER IN THE POSTGRADUATE EDUKATION - Сафарян, Світлана (SWorldJournal, 2022)
one of the important tasks of the national system of postgraduate education is to solve the problem of improving the language personality of a teacher with developed verbal and linguistic intelligence on the basis of an integrated approach in the process